Hypoglycemic effect of Phaleria macrocarpa (Scheff.) Boerl dry extract in healthy adults - Meiyanti, Meiyanti; Margo, Eveline; Pusparini, Pusparini; Merijanti, Lie Tanu; Lesmana, Alvina (Faculty of Medicine, Trisakti University, 2018)
BackgroundThe prevalence of diabetes in Indonesia continues to increase and causes many complications. Fruits of Phaleria macrocarpa (Scheff.) Boerl. (PM) are used in the traditional health system of the Indonesians, as effective remedy in the management of diabetes mellitus. The aim of this study was to evaluate the effect and magnitude of doses of PM dry fruit extract (PME) on blood glucose levels in healthy adults.MethodsThis research was of pre-posttest design involving 30 healthy volunteer subjects aged 20-55 years receiving glucose loads. At pre-test the subjects were given orally 75 g glucose, and at post-test they were given PME at doses of 125 mg and 250 mg. Data collection included anthropometric examination and blood glucose level. The area under the curve (AUC) of blood glucose levels was measured at 0, 15, 30, 60, 120 and 180 minutes. Data analysis was performed using paired t-test with p <0.05.ResultsThe percentage of reduction in AUC between pre- and post-test after administration of PME 125 mg was 12.1% and significant (p=0.000). But the percentage of reduction in AUC between pre- and post-test after administration of PME 250 mg was 4.07% and not significant (p=0.06). The reduction in AUC between post-test PME 125 mg vs PME 250 mg showed significant results (p=0.011).Conclusion This study demonstrated that a dose of 125 mg Phaleria macrocarpa (Scheff.) Boerl. dry extract has a hypoglycemic effect in healthy adults, and may therefore be suitable for use as traditional anti-diabetic drug.